Direct Ethanol Production from Breadfruit Starch (Artocarpus communis Forst.) by Engineered Simultaneous Saccharification and Fermentation (ESSF) using Microbes Consortium - Farida, Iftachul; Syamsu, Khaswar; Rahayuningsih, Mulyorini (Center of Biomass & Renewable Energy, Diponegoro University, 2015)
Breadfruit (Artocarpus communis Forst.) is one of sources for ethanol production, which has high starch content (89%). Ethanol production from breadfruit starch was conducted by Simultaneous Saccharification and Fermentation (SSF) technology using microbes consortium. The aim of the research was to examine a method to produce ethanol by SSF technology using microbes consortium at high yield and efficiency. The main research consisted of two treatments, namely normal SSF and enginereed SSF. The results showed that normal SSF using aeration and agitation during cultivation could produce ethanol at 11.15 Â± 0.18 g/L, with the yield of product (Yp/s) 0.34 g ethanol/g substrate; and yield of biomass (Yx/s) 0.29 g cell/g substrate, respectively. A better result was obtained using engineered SSF in which aeration was stopped after biomass condition has reached the end of the exponential phase. The ethanol produced was 12.75 Â± 0.04 g/L, with the yields of product (Yp/s) 0.41 g ethanol/g substrate, and the yield of cell (Yx/s) 0.09 g cell/g substrate.